Exploring the roles of AI-powered e-tutors in enhancing self-directed learning in open distance e-learning courses - Mncedisi Christian Maphalala; Rachel Gugu Mkhasibe; Dumsani Wilfred Mncube (Interdisciplinary Journal of Education Research)
Artificial Intelligence (AI) has ushered in a transformative era in education, particularly in the context of Open Distance e-Learning (ODeL). This paper explores the role of AI-powered e-tutors and their potential to revolutionise self-directed learning among students in ODeL courses in South Africa. Self-directed learning, a fundamental pillar of distance education, requires students to be proactive, independent, and motivated. Numerous studies in the fields of AI, ODeL, and Self-Directed Learning (SDL) were reviewed, including case studies involving ODeL institutions, to understand the role of AI-powered e-tutors. This research provides practical insights into using AI-powered e-tutoring to foster self-directed learning. The study allowed for the collection of relevant literature on the given topic that fits the pre-specified eligibility criteria and answers the formulated research questions. The findings underscore the transformative potential of AI-powered e-tutors, including personalised learning experiences, adaptive feedback, real-time support, increased learner engagement and motivation, and enhanced academic performance. The paper also addresses the practical challenges and limitations of implementing AI-powered e-tutoring, such as technology access, data privacy, and the continuous improvement of AI algorithms. The study contributes to the expanding knowledge of AI in education, providing practical insights for academics, policymakers, and technology developers, equipping them with the necessary information to leverage AI to strengthen self-directed learning in ODeL environments. It also outlines the practical implications for future research and practice, highlighting the potential of AI to revolutionise distance learning and empower learners to take control of their educational journeys.